Defining knowledge gaps in preterm birth research: Can biomarkers fill the gaps? - Williams, Scott M.; Rosenblatt, Kevin P.; Reznik, Sandra; Misra, Dawn P.; Siricilla, Shajila; Gomez-Lopez, Nardhy; Taylor, Brandie D.; Adams Waldorf, Kristina M.; Menon, Ramkumar; , PREBIC North America 2024; Helguera-Repetto, Addy Cecilia; Eastman, Alison; et al. (Frontiers in Medicine, 2025)
Preterm birth (PTB) is a syndrome arising from multiple etiologies that manifest as a final common phenotype, delivery before full term. Current knowledge gaps in epidemiologic, basic science, and clinical fields have limited our understanding of this complex pregnancy syndrome. Lack of insight into the cellular and molecular pathways underlying spontaneous PTB (PTB) has thus limited effective clinical management and restricted the investigation of novel treatments or druggable targets. Here, we examine several areas of domain-driven research that may lead to a better understanding of PTB, including infection and inflammation that drive early labor, social factors and their biological consequences that may affect or contribute to PTB risk, and current limitations affecting the development of novel pharmacological treatments. We discuss how the development of new biomarkers or panels of biomarkers can define PTB risk status and disease mechanisms and potentially lead to new therapies by bridging gaps between research domains often used to study PTB in relative isolation. We note that these panels may be population specific and it is critical to assess the heterogeneity of PTB in light of the variation among women of diverse backgrounds, both environmentally and genetically. Finally, we consider how complementary biomarkers from different PTB research domains could be integrated to design new diagnostic, preventative, and management options. Our hope is that new ways of looking at PTB can improve understanding of this common pregnancy complication leading to reduced global rates of PTB and improved outcomes for affected infants.